Human Dorsal Root Ganglia - Haberberger, Rainer Viktor; Barry, Christine; Dominguez, Nicholas; Matusica, Dusan (Frontiers in Cellular Neuroscience, 2019)
Sensory neurons with cell bodies situated in dorsal root ganglia convey information from external or internal sites of the body such as actual or potential harm, temperature or muscle length to the central nervous system. In recent years, large investigative efforts have worked towards an understanding of different types of DRG neurons at transcriptional, translational and functional levels. Those studies most commonly rely on data obtained from laboratory animals. Human DRG however, have received far less investigative focus over the last 30 years. Nevertheless, knowledge about human sensory neurons is critical for a translational research approach and future therapeutic development. This review aims to summarize both historical and emerging information about the size and location of human DRG, highlighting advances in the understanding of the neurochemical characteristics of human DRG neurons, in particular nociceptive neurons.